Riba and it’s Implications on the Low Prosperity of Small Traders in the Palopo City - Anwar, Suhardi M (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the real implications of Riba on the low welfare of small traders in Palopo City. The population used is small traders who sell in markets or on the roadside in the Palopo City area. The sampling method uses accidental sampling so that the total sample is 100 respondents. The data collection method is done by distributing questionnaires to respondents. To answer the above objectives, this study uses descriptive analysis and simple linear regression. But before testing the hypothesis the validity test and the questionnaire test were reliably tested on 20 people. The findings of this study are that Riba affects the low welfare of small traders. The average income of small traders is lower than expenses, so borrowing as a solution. Also, the coefficient of determination (R2)of 0.542 or 54.2%, indicating that the low welfare of small traders in the City of Palopo is affected by Riba by 54.2%. The rest is influenced by other factors.